Implementasi Restitusi Bagi Korban Tindak Pidana Perdagangan Orang - Sintia Maryam; Boedi Prasetyo (Dinasti Research, 2025)
Law Number 21 of 2007 highlights women and children as vulnerable groups in the crime of human trafficking (TPPO), which includes sexual exploitation, forced labor, and slavery, with perpetrators utilizing threats, violence, or fraud. The impacts are multidimensional, including physical, psychological, and socio-economic, so that restitution is presented as a mechanism for victim recovery through material and immaterial compensation. However, its implementation in Indonesia still faces obstacles, especially the lack of court attention to victims' rights, although the role of restitution is recognized as important to improve legal protection and encourage justice that is more in favor of victim recovery. This study uses a qualitative method that aims to understand the phenomenon as a whole based on the subject's experience, such as behavior, perception, motivation, and actions. The results of this study Human trafficking is a serious crime that causes physical, psychological, and economic losses to victims. Restitution, regulated in Law Number 21 of 2007 and related regulations, serves to restore victims' rights and ensure that perpetrators are held accountable. Involving LPSK, prosecutors, and courts, this mechanism not only compensates for material losses but also restores the dignity of victims, presenting justice that is more in favor of victim recovery in the criminal justice system.